Antenna design for wireless power transmission system - Loo, Bernard Beng Kiat (2015)
An antenna is designed for a wireless power transmission system for the purpose of energy harvesting. Energy harvesting is the process where energy is derived from the surroundings where in this case, would be focusing at radio waves. The patch antenna is the main component of the system; its physical design like size or shape affects is antenna parameters. For this project, the antenna will be designed to function with circular polarization at a center frequency of 2.4 GHz. The initial stage of the development will be conducted with simulation where the design will be based on a unique shape. The unique shape will be created in simulation, followed by having its physical dimensions will be varied and simulations will be conducted. For each simulation, the results are observed, followed by tuning and adjustment to attain the desired parameters. After desired parameters are attained, an e-shaped slotted-circular and a Tao-shaped slotted-circular patch antenna is proposed for circularly polarized (CP) radiation and RF energy harvesting. The e-shaped slotted-circular antenna is made up of an e-shaped slotted-circular patch radiator and a coaxial feed. An e-shaped slot is drilled in along the orthogonal axis of a circular patch to create circularly polarized radiation. The fabricated antenna is able to attain a gain over 5 dBic with circularly polarized radiation at 2.4 GHz. As for the Tao-shaped slotted-circular patch antenna, it is made up of a Tao-shaped slotted-circular patch and an aperture-coupled feeding structure. A Tao-shaped slot with its size and shape optimized is cut at the centre of the circular patch.